MicroRNA548ac expression level in relation to BDCAF scored Behçet's disease activity and history of treatment response - Sally S. Hassouna; Manal Y. Tayel; Ashraf I. Elzawawy; Rowayda M. Amin; Mona Tahoun (SpringerOpen, 2022)
Abstract Background Behçet's disease gives a challenge to be diagnosed and followed up due to lack of specific biomarkers. MicroRNAs showed relations to different disease states including immunological and inflammatory illnesses. In this study, we are estimating microRNA548ac levels for the first time to be tested in the disease to see if there is a link to disease activity and if microRNA548ac can be used as a biomarker for activity or remission and prognosis of Behçet's disease. MicroRNA548ac has been shown to have a role in autoimmunity and some inflammatory conditions. Blood samples were taken from patients to measure white blood cells expression of microRNA548ac, and compared to its expression in healthy subjects, disease activity was assessed by usage of Behçet's Disease Current Activity Form (BDCAF). Results MicroRNA548ac expression decreased but not significantly with increased Behçet's disease activity, and expression was having a significant positive correlation with increased treatment response history. Conclusions MicroRNA548ac appeared not to be related to disease activity which needs confirmation in further studies, but it may predict response to treatment so that patients having higher expression of microRNA548ac may have a better response to treatment. Here, microRNA548ac could be used as a disease biomarker for disease prognosis.